PENINGKATAN MOTIVASI BELAJAR INFORMATIKA MATERI SISTEM KOMPUTER MELALUI PLATFORM GIMKIT PADA SISWA KELAS 7 SMPN 15 MALANG - Wulandari, Rizka Safitri; Kirana, Kartika Candra; Purwanto, Eko Tristyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low student motivation in Informatics, particularly on Computer Systems, is a challenge in the digital era. This study aims to examine the effectiveness of the Gimkit platform in enhancing the motivation and activeness of 7th-grade students at SMPN 15 Malang. A quantitative approach with a quasi-experimental design was used. Instruments included an ARCS-based motivation questionnaire and an observation sheet. The findings show that students using Gimkit were more motivated and active than those in conventional classes. Gimkit was found effective in capturing attention, providing relevance, building confidence, and fostering learning satisfaction.